Artificial Intelligence Based Smart Agriculture Applications in Greenhouses - Karabay, Gozde Sena; Cavas, Mehmet (Institute of Electrical and Electronics Engineers Inc., 2024)
Artificial intelligence can make human-like decisions through big data analysis and machine learning algorithms, contributing to the autonomous management of processes. Smart farming transforms traditional agricultural methods by utilizing technologies such as artificial intelligence, machine learning, deep learning, and the Internet of Things (IoT) to increase efficiency and sustainability in agricultural production. Traditional farming methods are inadequate in the face of climate change, dwindling water resources, and a growing global population. In this context, smart farming offers solutions by enabling more efficient use of resources, improving product quality, reducing greenhouse gases, and optimizing agricultural processes. Smart farming applications provide farmers with many conveniences, such as real-time monitoring of crop development, early warning for disease and pest detection, and automatic irrigation. This study discusses the technologies and sensors used in smart farming and greenhouse cultivation, the Internet of Things and its application areas in smart farming, and artificial intelligence, deep learning, machine learning, and the algorithms used in machine learning. © 2024 IEEE.
Seralarda Yapay Zek Tabanli Akilli Tarim Uygulamalari
8th International Artificial Intelligence and Data Processing Symposium, IDAP 2024 -- 21 September 2024 through 22 September 2024 -- Malatya -- 203423
Keywords: Artificial Intelligence; Greenhouse Cultivation; Internet of Things; Smart Agriculture